Congenital cataract in newborns: A qualitative study on parents' experiences of the surgery and subsequent care. Issue 6 (19th March 2020) - De Lima, Sara; Kugelberg, Maria; Jirwe, Maria
Abstract: Purpose: Having a child with congenital cataract that requires surgery, contact lens treatment, and frequent medication is a life‐altering experience. The aim of this study was to provide more in‐depth knowledge of parents' experiences of diagnosis, surgery, and subsequent care, in order to find the areas for improvement. Methods: Data were collected via semi‐structured interviews with parents recruited from St. Erik Eye Hospital, Sweden. The children were operated for congenital cataract before 3 months of age and were aged 12–24 months at the time of the interviews. The interviews were analysed using qualitative content analysis with an inductive approach. Results: Three themes emerged from the data: living in a turbulent time before the diagnosis, coping during the time of initial treatment, and managing the responsibility of their child's visual development. All parents expressed confidence in the operating unit. However, there was a clear need for reliable information on the condition, the surgery, and likely the long‐term outcome in the time between receiving the preliminary diagnosis at the maternity ward and getting it confirmed by a paediatric ophthalmologist. Conclusion: Much of the parents' concern in this turbulent time is linked to poor information before the visit to the eye hospital. We, therefore, recommend earlier contact with the eye hospital, preferably at the time of writing the referral. Moreover, the possibility of providing up‐to‐date information via alternative information channels such as smartphone apps should be investigated.